Affordances in Mobile Augmented Reality Applications - Gjøsæter, Tor (International Journal of Interactive Mobile Technologies (iJIM), 2014)
This paper explores the affordances of augmented reality content in a mobile augmented reality application. A user study was conducted by performing a multi-camera video recording of seven think aloud sessions. The think aloud sessions consisted of individual users performing tasks, exploring and experiencing a mobile augmented reality (MAR) application we developed for the iOS platform named ARad. We discuss the instrumental affordances we observed when users interacted with augmented reality content, as well as more complex affordances rising from conventions from media content, AR and the traditional WIMP paradigm. We find that remediation of traditional newspaper content through the MAR medium can provide engaging, pleasing and exciting user experiences. However, the some of the content still suffers from being shoveled onto the MAR platform without adapting it properly. Finally, we discuss what content was most successfully mediated to the user and how the content impacts the user experience.